Pengembangan Bahasa AUD melalui Metode Bercerita - Noviany, Dhea Alifa; Arkam, Rohmad; Haryadi, Rochmad (MENTARI: Jurnal Pendidikan Anak Usia Dini, 2024)
Early age is an important phase for a child’s development stage. Therefore, it is very important for children to do this as optimally as possible during this period, especially aspects of language development. One form of language development is through telling stories with picture story books. This article wants to describe the implementation of language development activities through storytelling with picture story books in group B at RA. ‘Aisyiyah Sidoharjo, Pulung, Ponorogo. The method used in this research is descriptive qualitative, observation, interviews and documentation are the techniques used in data collection. The research results show that the steps in implementing language development through picture story books in group B RA. ‘Aisyiyah, Sidoharjo, Pulung, Ponorogo carried out several processes, namely; setting learning objectives; carry out learning planning; designing learning activities; organizing time and space; carrying out evaluations and assessments; reflect and improve the learning process. Picture storybook media is very appropriate to use for developing aspects of children’s language because through storytelling children are able to express what they feel and see.